2012
DOI: 10.1007/s11481-012-9392-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation, Neuroautoimmunity, and the Co-Morbidities of Complex Regional Pain Syndrome

Abstract: Complex Regional Pain Syndrome (CRPS) is associated with non-dermatomal patterns of pain, unusual movement disorders, and somatovisceral dysfunctions. These symptoms are viewed by some neurologists and psychiatrists as being psychogenic in origin. Recent evidence, however, suggests that an autoimmune attack on self-antigens found in the peripheral and central nervous system may underlie a number of CRPS symptoms. From both animal and human studies, evidence is accumulating that neuroinflammation can spread, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 161 publications
1
31
0
Order By: Relevance
“…Although the mechanisms are unclear, chronic, nonresolving inflammation in CRPS is characterized by prolonged secretion of proinflammatory factors, disruption of the blood–brain barrier, and development of autoimmunity [17]. The pain and inflammation in CRPS are not alleviated by commonly used analgesics or anti-inflammatory drugs, and the development of persistent pain states and the maintenance of chronic inflammation point to systemic aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms are unclear, chronic, nonresolving inflammation in CRPS is characterized by prolonged secretion of proinflammatory factors, disruption of the blood–brain barrier, and development of autoimmunity [17]. The pain and inflammation in CRPS are not alleviated by commonly used analgesics or anti-inflammatory drugs, and the development of persistent pain states and the maintenance of chronic inflammation point to systemic aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…The agents entering the OB may spread further in the brain to cause neurological disorders. It is suggested that inflammatory responses can spread in the CNS both anterogradely or retrogradely via axonal projections (81). For instance, corneal inflammation induced by instillation of benzalkonium chloride damages primary sensory neurons in the trigeminal ganglion, leading to the activation of second-order neurons and glial cells in the brain stem and to the production of pro-inflammatory cytokines (82).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one important methodological aspect of the current study is that we directly injected corticosteroids into the thoracic sympathetic ganglion. Autoimmune attack against peripheral nerves might trigger leukocyte extravasation, autoantibody exudation, neuroinflammation, and neuroimmune activation in associated dorsal root ganglia, sympathetic ganglion, and the spinal cord, and this has been suggested as a possible underlying mechanism of the development of CRPS [5,13,23,30,34,54]. There are data supporting pain improvement in CRPS patients after the use of systemic steroids [11,19,28].…”
Section: Discussionmentioning
confidence: 99%